Perancangan Aplikasi Pengenalan Alat Musik Tradisional Nusantara Berbasis Android - Wahyuzi Andriansyah; Ali Sadikin (Jurnal PROCESSOR, 2017)
Traditional music is a music that develop across the archipelago and is a here dictary practice which is still on the run in society. The music is scattered almost all over and every region have different characteristics. Musical archipelago is born, grows, and develops throughout the archipelago. But the public interest to learn and know traditional musical instruments have begun to decrease because the traditional musical instruments are considered ancient and out of date so they are reluctant to learn it. One way for people to know as well as learning the traditional musical instrument is by creating an introduction application of traditional musical instruments archipelago based android instrument made in 3D to make it interesting interest of the community to learn it. System modeling On the construction of this application use UML (Unified Modelling Language) with tools activity diagram, use case And developed using the model waterfall Which is run on android operating system. This app is expected Can be an appropriate tool So that people want to Learn the traditional musical instruments archipelago.